1997
DOI: 10.1002/(sici)1097-461x(1997)63:2<585::aid-qua28>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Resonance in catacondensed benzenoid hydrocarbons

Abstract: We consider resonance in cata-condensed benzenoids having six and seven fused benzene rings. The resonance relationship between the Kekule valence structures of the molecules is represented by the resonance graphs in which the vertices represent the Kekule valence structures, and the edges, the presence of the quantum Ž chemical resonance integral involving permutation of three CC double bonds within a . single six-membered ring . The construction of the resonance graphs for large benzenoids is outlined and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…3. The concept of the resonance graph appears to be very natural in chemistry, see [17,18] and the arguments from the introduction of [10]. The structure of the resonance graphs of hexagonal graphs was closely examined in [11] where the so called decomposition theorem is proved.…”
Section: Theorem 1 Let G Be An Arbitrary Fibonaccene With H Hexagonsmentioning
confidence: 99%
“…3. The concept of the resonance graph appears to be very natural in chemistry, see [17,18] and the arguments from the introduction of [10]. The structure of the resonance graphs of hexagonal graphs was closely examined in [11] where the so called decomposition theorem is proved.…”
Section: Theorem 1 Let G Be An Arbitrary Fibonaccene With H Hexagonsmentioning
confidence: 99%
“…The Z-transformation graph (also called resonance graph) is introduced independently by Gründler [10], Zhang et al [37], Randić [26] and Fournier [7], and widely studied by Zhang and Zhang [44,45], Kalvažar et al [15,16,17], Lam and Zhang [20], Zhang et al [38,40,42] andŽigert Pleteršek [47,48]. Recently, Zhang et al [41] introduced the concept of matchable distributive lattice and got some consequences on matchable distributive lattices, Yao and Zhang [34] obtained some results on non-matchable distributive lattices with a cut-element.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980 ′ s there have been developed a combinatorial object, the Z-transformation graph (or resonance graph) [23,24] on the set perfect matchings of a hexagonal system, late extended to a general plane bipartite graph [27,33,34,35]; see a recent survey [29]. Randić [15,16] showed that the leading eigenvalue of the resonance graphs has a quite satisfactory correlation with the resonance energy of benzenoid hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%